LO70: Functional & cognitive decline in older delirious adults after an emergency department visit. (May 2019) - Giroux, M.; Sirois, M.; Nadeau, A.; Boucher, V.; Carmichael, P.; Voyer, P.; Pelletier, M.; Gouin, É.; Daoust, R.; Berthelot, S.; Lamontagne, M.; Morin, M.; et al.
Abstract : Introduction : While negative consequences of incident delirium on functional and cognitive decline have been widely studied, very limited data is available regarding functional and cognitive outcomes in Emergency Department (ED) patients. The aim of this study was therefore to evaluate the impact of ED stay-associated delirium on older patient's functional and cognitive status at 60 days post-ED visit.Methods : This study is a planned sub-analysis of a large multicentre prospective cohort study (the INDEED study). This project took place between March and July of the years 2015 and 2016 within 5 participating EDs across the province of Quebec. Independent non-delirious patients aged □65, with an ED stay at least 8hrs were monitored until 24hrs post-ward admission. A 60-day follow-up phone assessment was also conducted. Participants were screened for delirium using the validated Confusion Assessment Method (CAM) and the severity of its symptoms was measured using the Delirium Index. Functional and cognitive status were assessed at baseline as well as at the 60-day follow-up using the validated OARS and TICS-m.Results : A total of 608 patients were recruited, 393 of which completed the 60-day follow-up. Sixty-nine patients obtained a positive CAM during ED-stay or within the first 24 hours following ward admission. At 60-days, those patients experienced a loss of 3.1 (S.D. 4.0) points on the OARS scale compared to non-delirious patients who lost 1.6 (S.D. 3.0) (p = 0.03). A significant difference in cognitive function was also noted at 60-days, as delirious patients' TICS-m score decreased by 2.1 (S.D. 6.2) compared to non-delirious patients, who showed a minor improvement of 0.5 (S.D. 5.8) (p = 0.01).Conclusion : People who developed ED stay-associated delirium have lower baseline functional and cognitive status than non-delirious patients and they will experience a more significant decline at 60 days post-ED visit.